Reflective Inquiry Learning for Early Childhood Neuroplasticity: A Neuroscience Approach in the Indonesia–Papua Border - Harahap, Dharma Gyta Sari; Muh. Rafi'y; Ferry Irawan; Cristiana Normalita de Lima; Riyana, Minuk (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2025)
Inclusive education in the Indonesia–Papua New Guinea border region faces complex challenges, particularly in providing optimal learning services for Early Childhood Education (ECE). This study aims to analyze the effectiveness of the Neuroscience-Based Reflective Inquiry Learning (RIL) model in optimizing neuroplasticity among young children in border areas. Recent neuroscience studies have highlighted the profound influence of multisensory experiences, emotional engagement, and social interaction on early childhood neuroplasticity. This research employed a qualitative design using classroom action research in a border-area preschool in Papua. Collected data through observation, interviews, and documentation, and analyzed using Miles & Huberman's interactive model. The findings reveal that neuroscience-based RIL significantly enhances children's cognitive, emotional, and social stimulation. Quantitative outcomes indicated improvements in prosocial behavior (35%), reductions in aggressive behavior (20%), and a decrease in withdrawn behavior (15%). Moreover, the involvement of teachers and parents in reflective learning processes further reinforced the model's effectiveness. The analysis also confirmed that integrating neuroscience-informed practices, such as multisensory learning and trauma-sensitive approaches, supports the adaptive development of children's executive functions. This study concludes that neuroscience-based RIL is a promising pedagogical model for optimizing neuroplasticity in early childhood, particularly in border regions with limited access to quality education. The findings contribute theoretically to the field of neuroscience-informed inclusive education and practically to policy and practice recommendations for teachers and stakeholders in border communities.